2001
DOI: 10.1038/35059110
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of haemagglutinins on virus-infected cells by NKp46 activates lysis by human NK cells

Abstract: Natural killer (NK) cells destroy virus-infected and tumour cells, apparently without the need for previous antigen stimulation. In part, target cells are recognized by their diminished expression of major histocompatibility complex (MHC) class I molecules, which normally interact with inhibitory receptors on the NK cell surface. NK cells also express triggering receptors that are specific for non-MHC ligands; but the nature of the ligands recognized on target cells is undefined. NKp46 is thought to be the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
802
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 842 publications
(835 citation statements)
references
References 29 publications
30
802
3
Order By: Relevance
“…Moreover, we found that intrahepatic frequency of NKp46 High NK cells inversely correlated with HCV loads. Whether NKp46 recognizes a HCV-derived protein [17][18][19][20][21] or interacts with a yet unknown NKp46 ligand, as has been suggested for malignant transformed cells, 40,41 remains to be clarified. However, blocking of NKp46 significantly reduced the capability of both circulating and intrahepatic NK cells to block HCV replication, suggesting a role of NKp46 in the regulation of anti-HCV immune responses.…”
Section: Nk Cells (Supportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that intrahepatic frequency of NKp46 High NK cells inversely correlated with HCV loads. Whether NKp46 recognizes a HCV-derived protein [17][18][19][20][21] or interacts with a yet unknown NKp46 ligand, as has been suggested for malignant transformed cells, 40,41 remains to be clarified. However, blocking of NKp46 significantly reduced the capability of both circulating and intrahepatic NK cells to block HCV replication, suggesting a role of NKp46 in the regulation of anti-HCV immune responses.…”
Section: Nk Cells (Supportingmentioning
confidence: 99%
“…Moreover, NKp46 plays an important role in the killing of virus-infected cells by interacting with viral proteins. [17][18][19][20][21] Studies on NKp46 in HCV infection are controversial, because both reduced and increased surface expression have been reported. 5,[7][8][9] In this context, it is of interest that earlier studies showed that the surface expression of NKp46 may vary in different human peripheral blood NK cells, and that the NKp46 phenotype of NK clones correlates with cytolytic activity.…”
mentioning
confidence: 99%
“…Of the latter, NKp46 and NKp30 are on most human peripheral blood NK cells, whereas, NKp44 is only on activated NK cells (37,42). Although endogenous natural cytotoxicity receptor ligands remain undetermined, NKp46 binds the influenza hemagglutinin (HA) protein as well as the HA-neuraminidase of parainfluenzavirus (43,44). NKG2D mediates NK cytolysis of tumors and CMVinfected cells (45,46).…”
Section: Nkp46 and Nkg2d Recognition Of Infected Dendritic Cells Is Nmentioning
confidence: 99%
“…5-7 NKp46 is encoded by Ncr1 and associates with the ITAM-containing CD3ζ or FcRγ polypeptides. Several endogenous ligands of NKp46 have been described including the complement factor P, 8 the intracellular filamentous cytoskeletal protein vimentin expressed on the surface of Mycobacterium tuberculosis –infected monocytes, 9 and several viral proteins such as hemagglutinin and hemagglutinin neuraminidases of the influenza, 10,11 Sendai, 12 Newcastle disease, 13 ectromelia and vaccinia viruses. 14 NKp46 was also shown to recognize PfEMP1 of Plasmodium falciparum , 14 an unknown ligand from Fusobacterium nucleatum , 15 adhesins from Candida glabrata .…”
Section: Introductionmentioning
confidence: 99%